Modification of Pyrimidine and Purine Nucleotides By "Click" Chemistry: Design, Synthesis and Properties Study - (:unkn) unknown (My University, 2014)
This dissertation consists of three main parts, totaling five chapters, and focuses on developing novel nucleosides via "click" chemistry and studying their potential biological properties. Chapter three describes the synthesis and properties of coumarin-modified fluorescent DNAs. Coumarin-modified 2'-deoxythymidine was synthesizedvia "click" chemistry and incorporated into oligodeoxynucleotides (ODNs) which induce photoreversible interstrand cross-link (ICL) upon 350/254 nm photoirradiation. The irradiation at 350 nminduces DNA cross-linking with ODNs containing coumarin. The cross-linked DNA products formed from coumarin are not fluorescent. Further investigation showed that coumarin moiety undergoes the (2π+2π) photocycloaddition with 2'-deoxythymidine (dT), 2'-deoxycytidine (dC), and to a much lower extent, 2'-deoxyadenine (dA). As an additional ability, ICL materialwas observedto be reverted to their original single stranded ODN by a ring-opening reaction upon irradiation at 254 nm without the addition of any chemical reagents. After the successful discovery of the photo-reversible DNA cross-linking ability of coumarin-modified dT, coumarin was conjugated to dA and dC to examine the generality of this phenomina. This part is discussed in chapter four. In the fifth chapter, triazole- and phenyltriazole-modified dT were synthesized and incorporated into ODNs by solid phase DNA synthesis. Similar to the canonical nucleosides, the modified nucleoside scaffolds maintain Watson-Crick hydrogen bonding formation. Thephysic-chemical and biological properties of triazole-containing ODN duplexes were investigated.